2020
DOI: 10.1002/jlcr.3872
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis of a Bruton's tyrosine kinase inhibitor, [11C]Tolebrutinib, via palladium‐NiXantphos‐mediated carbonylation

Abstract: Bruton's tyrosine kinase (BTK) is a key component in the B‐cell receptor signaling pathway and is consequently a target for in vivo imaging of B‐cell malignancies as well as in multiple sclerosis (MS) with positron emission tomography (PET). A recent Phase 2b study with Sanofi's BTK inhibitor, Tolebrutinib (also known as [a.k.a.] SAR442168, PRN2246, or BTK'168) showed significantly reduced disease activity associated with MS. Herein, we report the radiosynthesis of [11C]Tolebrutinib ([11C]5) as a potential PET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…We hypothesized that these challenges could be alleviated by leveraging the more ready availability of [ 11 C]CO from modern cyclotrons (e.g., utilizing the Process Cabinet of a GE PETtrace) and developing methods that are compatible with the automated synthesis modules used for cGMP manufacture of PET radiotracers today. Thus, we and others are motivated to develop more user-friendly approaches for 11 C-carbonylation (28,(39)(40)(41). Notably, concurrent with our efforts, Lindberg et al demonstrated that [ 11 C]ibrutinib can be prepared via 11 C-carbonylation in a reactor method (40), and reported preliminary pre-clinical imaging results comparable to our earlier findings (29).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…We hypothesized that these challenges could be alleviated by leveraging the more ready availability of [ 11 C]CO from modern cyclotrons (e.g., utilizing the Process Cabinet of a GE PETtrace) and developing methods that are compatible with the automated synthesis modules used for cGMP manufacture of PET radiotracers today. Thus, we and others are motivated to develop more user-friendly approaches for 11 C-carbonylation (28,(39)(40)(41). Notably, concurrent with our efforts, Lindberg et al demonstrated that [ 11 C]ibrutinib can be prepared via 11 C-carbonylation in a reactor method (40), and reported preliminary pre-clinical imaging results comparable to our earlier findings (29).…”
Section: Introductionsupporting
confidence: 70%
“…When considering how to prepare PET isotopologs of ibrutinib, tolebrutinib, and evobrutinib, it is necessary to utilize carbon-11 (t 1/2 = 20 min) given the impractically short halflives of oxygen-15 and nitrogen-13 (t 1/2 = 2 min and 10 min, respectively). The structures of the BTK inhibitors in question offer a limited opportunity for incorporating carbon-11 into these scaffolds and, as such, we reasoned that labeling the carbonyl group of the acrylamide moiety was most likely to be successful because of synthetic accessibility of the requisite precursors and precedent for synthesizing [ 11 C]acrylic acid derivatives (24)(25)(26)(27)(28). When our teams set out in a campaign to prepare [ 11 (29).…”
Section: Introductionmentioning
confidence: 99%
“…The radiosynthesis of [ 11 C]ibrutinib was fully automated using a commercial TracerMaker TM 11 C synthesis platform. The method and setup of the automated synthesis platform were adapted with only minor changes from our previously published method for [ 11 C]tolebrutinib (15). Commercially available anhydrous tetrahydrofuran (THF) solvent was used, eliminating the need for freshly distilled THF, and the semi-preparative high-performance liquid chromatography (HPLC) employed a flow rate of 6.0 ml/min.…”
Section: Radiosynthesis Of [ 11 C]ibrutinibmentioning
confidence: 99%
“…Although ibrutinib has not been studied clinically as a BTK inhibitor in MS, it has shown efficacy in other autoimmune diseases, such as arthritis, lupus, and recently in treatment of COVID-19 (SARS-CoV-2) (11)(12)(13)(14). The versatility of BTK inhibitors, such as ibrutinib, in treating various B-cell-related diseases has led to their development as radiotracers for positron emission tomography (PET) (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…It showed excellent selectivity for BTK over a number of kinases, except for BLK, BMX, TEC and ERBB4 (IC 50 : 0.6, 1.1, 1.0, and 1.0 nM, respectively). Notably, this BTK inhibitor was demonstrated to provide dose-dependent protection from MS induced in a mouse model of experimental autoimmune encephalomyelitis (EAE) [ 59 ]. MS is a chronic inflammatory degenerative disorder, affecting more than 2.3 million people around the world, which results from the gradual destruction of the myelin sheaths that protect nerve cells, and of the nerve cells themselves.…”
Section: Current Development Of Btk Inhibitors For the Treatment Of Autoimmune And Inflammatory Diseasesmentioning
confidence: 99%